6x+36=3x+76

Simple and best practice solution for 6x+36=3x+76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+36=3x+76 equation:


Simplifying
6x + 36 = 3x + 76

Reorder the terms:
36 + 6x = 3x + 76

Reorder the terms:
36 + 6x = 76 + 3x

Solving
36 + 6x = 76 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
36 + 6x + -3x = 76 + 3x + -3x

Combine like terms: 6x + -3x = 3x
36 + 3x = 76 + 3x + -3x

Combine like terms: 3x + -3x = 0
36 + 3x = 76 + 0
36 + 3x = 76

Add '-36' to each side of the equation.
36 + -36 + 3x = 76 + -36

Combine like terms: 36 + -36 = 0
0 + 3x = 76 + -36
3x = 76 + -36

Combine like terms: 76 + -36 = 40
3x = 40

Divide each side by '3'.
x = 13.33333333

Simplifying
x = 13.33333333

See similar equations:

| z^2+(z+3)i+1=0 | | e^3-5x=531 | | 2x^3+3x^2+20=0 | | (m-5)(5m+3)=0 | | X^2-10x-3=-12 | | ln(y)=2x+5 | | (5x-3)+log(4)*(9-x)=3 | | (16x^2+36)= | | v=-3i | | (x-(0.21x))0.25=555.56 | | 0.1x-x=500 | | (x-(0.21x))0.25=500 | | 6r+7=22 | | 9x+7x-4x-5=55 | | xy+3x-7y-21=0 | | 3ax-11a=-3 | | 32r^2-112r+80=0 | | 2.5a+2b= | | 8x-6y=15 | | 500=((x-(0.21x))0.25)-0.1 | | 44x^2-39x+9=0 | | 39x^2-31x+6=0 | | (4b^2-4b)=0 | | 500=(x-(0.21x))0.25 | | (9b^2-81)=0 | | 4x-2(12x-x)=18 | | y^2-2x-6y+13=0 | | Sin(6x)*cos(6x)+1=0 | | Sin(6x)*cos(6x)-1=0 | | 8x-32=128-2x | | 8x-32=128+2x | | 8x-2x=128-32 |

Equations solver categories